Estilos de docência em narrativas de professores e professoras de matemática - Maria Jose de Paula (2007)
This work searches for, and elucidates Mathematics teachers teaching stiles, focusing elements, dimensions, factors and circumstances associated to this styles. Identifies usual elements on the teachers styles and what is particular to each one of them. Proving that the styles are hybrid, changeable and mutant, theres been no purpose of framing teachers actions and speech into models, classifications or typologies. Theoretical- methodological basis has been found on researcher like Arroyo, Josso, Nóvoa and Teixeira, who call attention to teachers lives and work or refer to culture, representations and social cultural experiences of the teachers. While interpreting this styles, four teaching dimensions were given priority: a) rituals, practices and actions developed by teachers during classes; b) teachers conceptions related to their students and relations, interactions and acquaintance; c) professional dimensions related to the ways that teachers understand and signify their profession and work; d) conceptions, point of views and postures toward Mathematic, understandings related to mathematical knowledge, structure, value, utility. Data were collected through narrative interview of three male and two female teachers of elementary school. The narratives were recorded, transcripted and textualized, transforming into research material. Having the theoretical reference and understanding teaching styles as the way of being and developing teaching, we questioned that teaching styles are formed on the confluence of several elements, factors and circumstances related to school, teachers and students. Are constituted by an institutional social-historic reality, presenting impersonal and formal computes, peculiar to bureaucratic organizations. The styles relate to the teacher sociological profile, besides subjective factors related to the point of view, representations and the teachers relation with teaching. And also connects to the students profile, age, social and class origin